Wood at home - Pauwels, Jo ([Enghien, Belgium] : Beta-Plus, 2011)
"Wood is a noble material, which offers many advantages in the home: natural effect, enregy-friendliness, recyvlable and a very warm and intimate emanation. This book usues hundreds of inspiring photos to show the many uses of wood in the home. Much attention is also paid to wooden constructions:recently completeld projects by well known companies."
1. Mastery in wooden plank floors -- 2. Perfect harmony -- 3. A warm and contemporary rectory-style house -- 4. Rebellious and artistic -- 5. Traditional craftsmanship in a modern living environment -- 6. Weather-worn material is given new life -- 7. Authentic charm, modern living comfort -- 8. A special merger -- 9. Warm feel in an austere design -- 10. Perfection down to the finest details -- 11. A country house with a lived-in character -- 12. Kitchen designs made to measure for every client -- 13. Trendsetting in solid wood construction -- 14. The art of living in the mountains, "key on the door" -- 15. the charm of English inspired outbuildings -- 16. A real holiday feeling
Translated from the French
Keywords: Wood in interior decoration -- Pictorial works